Early development of porcine parthenogenetic embryos and reduced expression of primed pluripotent marker genes under the effect of lysophosphatidic acid. (5th July 2018) - Zhu, Xiusheng; Li, Lanyu; Gao, Bangjun; Zhang, Dandan; Ren, Yanyan; Zheng, Beibei; Li, Mengmei; Shi, Deshun; Huang, Ben
Abstract: To further promote the early development of porcine embryos and capture "naïve" pluripotent state within blastocyst, the experiment explored the effects of lysophosphatidic acid (LPA) on the early development of porcine parthenogenetic embryos and the expression of pluripotency relevant genes. The results showed that the addition of 50 μM LPA significantly improved parthenogenetic embryo cleavage rate (82.7% vs. 74.7%, p < 0.05), blastocyst rate (24.5% vs. 11.3%, p < 0.05) and blastocyst cell count (56 ± 7.9 vs. 42 ± 1.0, p < 0.05) than that of the control group. In addition, immunostaining experiment determined that the fluorescence intensity of OCT4 was also significantly higher than that of the control group. The quantitative real‐time polymerase chain reaction (qRT–PCR) test revealed that addition of 50 μM LPA could significantly enhance the expression level of pluripotent gene OCT4 and trophoblast marker genes CDX2, however, decrease the expression of primitive hypoblast marker gene GATA4 . The results also indicated that LPA might decrease the expression of GATA4 through the ROCK signalling pathway. For further investigating the effect of the addition of LPA on the expression of "primed" and "naïve" genes, we also detected the expression of those pluripotency‐related genes by qRT–PCR. The results showed addition of LPA had no significant effect on the expression of "naïve" pluripotent genes, but it was able to significantly decrease the expression of "primed" pluripotent genes, NODAL and Activin‐A; furthermore, it also could significantly improve the expression of OCT4 and c‐Myc which act as two important ES cell renewal factors. Above all, the addition of LPA can facilitate the early development of porcine parthenogenetic embryos, which may be able to benefit for capturing "naïve" pluripotency in vitro through inhibiting "primed" pluripotency.